Binding of SEC11 Indicates Its Role in SNARE Recycling after Vesicle Fusion and Identifies Two Pathways for Vesicular Traffic to the Plasma Membrane. Issue 3 (6th March 2015) - Karnik, Rucha; Zhang, Ben; Waghmare, Sakharam; Aderhold, Christin; Grefen, Christopher; Blatt, Michael R.
Abstract : A protein that regulates secretion targets one of two homologous and functionally overlapping SNARE (vesicle trafficking) proteins in Arabidopsis to drive traffic and is important for recycling of the SNARE complex. Abstract: SNARE (soluble N -ethylmaleimide-sensitive factor attachment protein receptor) proteins drive vesicle fusion in all eukaryotes and contribute to homeostasis, pathogen defense, cell expansion, and growth in plants. Two homologous SNAREs, SYP121 (=SYR1/PEN1) and SYP122, dominate secretory traffic to the Arabidopsis thaliana plasma membrane. Although these proteins overlap functionally, differences between SYP121 and SYP122 have surfaced, suggesting that they mark two discrete pathways for vesicular traffic. The SNAREs share primary cognate partners, which has made separating their respective control mechanisms difficult. Here, we show that the regulatory protein SEC11 (=KEULE) binds selectively with SYP121 to affect secretory traffic mediated by this SNARE. SEC11 rescued traffic block by dominant-negative (inhibitory) fragments of both SNAREs, but only in plants expressing the native SYP121. Traffic and its rescue were sensitive to mutations affecting SEC11 interaction with the N terminus of SYP121. Furthermore, the domain of SEC11 that bound the SYP121 N terminus was itself able to block secretory traffic in the wild type and syp122 but not in syp121 mutant Arabidopsis. Thus, SEC11 binds and selectively regulates secretory traffic mediated by SYP121 and is important for recycling of the SNARE and its cognate partners.